HIV-1 transgene expression in rats causes oxidant stress and alveolar epithelial barrier dysfunction - Lassiter, Coy (BioMed Central, 2009)
BACKGROUND: HIV-infected individuals are at increased risk for acute and chronic airway disease even though there is no evidence that the virus can infect the lung epithelium. Although HIV-related proteins including gp120 and Tat can directly cause oxidant stress and cellular dysfunction, their effects in the lung are unknown. The goal of this study was to determine the effects of HIV-1 transgene expression in rats on alveolar epithelial barrier function. Alveolar epithelial barrier function was assessed by determining lung liquid clearance in vivo and alveolar epithelial monolayer permeability in vitro. Oxidant stress in the alveolar space was determined by measuring the glutathione redox couple by high performance liquid chromatography, and the expression and membrane localization of key tight junction proteins were assessed. Finally, the direct effects of the HIV-related proteins gp120 and Tat on alveolar epithelial barrier formation and tight junction protein expression were determined. RESULTS: HIV-1 transgene expression caused oxidant stress within the alveolar space and impaired epithelial barrier function even though there was no evidence of overt inflammation within the airways. The expression and membrane localization of the tight junction proteins zonula occludens-1 and occludin were decreased in alveolar epithelial cells from HIV-1 transgenic rats. Further, treating alveolar epithelial monolayers from wild type rats in vitro with recombinant gp120 or Tat for 24 hours reproduced many of the effects on zonula occludens-1 and occludin expression and membrane localization. CONCLUSION: Taken together, these data indicate that HIV-related proteins cause oxidant stress and alter the expression of critical tight junction proteins in the alveolar epithelium, resulting in barrier dysfunction.